Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve the inequality [tex]\(-3(x-3) \leq 5(1-x)\)[/tex], let's proceed step-by-step:
1. Expand both sides of the inequality:
Let's first expand the expressions on both sides of the inequality.
[tex]\[ -3(x - 3) \leq 5(1 - x) \][/tex]
For the left side:
[tex]\[ -3(x - 3) = -3x + 9 \][/tex]
For the right side:
[tex]\[ 5(1 - x) = 5 - 5x \][/tex]
2. Rewrite the inequality with the expanded expressions:
Now we have:
[tex]\[ -3x + 9 \leq 5 - 5x \][/tex]
3. Isolate the terms involving [tex]\(x\)[/tex] on one side of the inequality:
To simplify, let's add [tex]\(5x\)[/tex] to both sides:
[tex]\[ -3x + 5x + 9 \leq 5 - 5x + 5x \][/tex]
Which simplifies to:
[tex]\[ 2x + 9 \leq 5 \][/tex]
4. Isolate the constant term on the other side:
Subtract 9 from both sides:
[tex]\[ 2x + 9 - 9 \leq 5 - 9 \][/tex]
Which simplifies to:
[tex]\[ 2x \leq -4 \][/tex]
5. Solve for [tex]\(x\)[/tex]:
Finally, divide both sides by 2:
[tex]\[ x \leq \frac{-4}{2} \][/tex]
[tex]\[ x \leq -2 \][/tex]
Thus, the solution to the inequality [tex]\(-3(x-3) \leq 5(1-x)\)[/tex] is [tex]\(x \leq -2\)[/tex].
The correct answer is:
[tex]\[ \boxed{\text{C. } x \leq -2} \][/tex]
1. Expand both sides of the inequality:
Let's first expand the expressions on both sides of the inequality.
[tex]\[ -3(x - 3) \leq 5(1 - x) \][/tex]
For the left side:
[tex]\[ -3(x - 3) = -3x + 9 \][/tex]
For the right side:
[tex]\[ 5(1 - x) = 5 - 5x \][/tex]
2. Rewrite the inequality with the expanded expressions:
Now we have:
[tex]\[ -3x + 9 \leq 5 - 5x \][/tex]
3. Isolate the terms involving [tex]\(x\)[/tex] on one side of the inequality:
To simplify, let's add [tex]\(5x\)[/tex] to both sides:
[tex]\[ -3x + 5x + 9 \leq 5 - 5x + 5x \][/tex]
Which simplifies to:
[tex]\[ 2x + 9 \leq 5 \][/tex]
4. Isolate the constant term on the other side:
Subtract 9 from both sides:
[tex]\[ 2x + 9 - 9 \leq 5 - 9 \][/tex]
Which simplifies to:
[tex]\[ 2x \leq -4 \][/tex]
5. Solve for [tex]\(x\)[/tex]:
Finally, divide both sides by 2:
[tex]\[ x \leq \frac{-4}{2} \][/tex]
[tex]\[ x \leq -2 \][/tex]
Thus, the solution to the inequality [tex]\(-3(x-3) \leq 5(1-x)\)[/tex] is [tex]\(x \leq -2\)[/tex].
The correct answer is:
[tex]\[ \boxed{\text{C. } x \leq -2} \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.